703 eaudiobook How i lost more than a quarter ton and gained a life. - Makin, Nancy (Tantor Media, 2010)
Nancy Makin weighed an astounding 703 pounds in May 2000. She was forty-five years old and had diabetes and heart disease. Thanks in equal parts to shame and logistics, she'd been homebound for a dozen years. But all that changed after a gift from her sister: a computer. A technophobe, Nancy ignored it for months, until finally boredom and curiosity pushed her into cyberspace. And there, in a chat room, she found the friendliness, the support, and even the love she'd been missing for so long. Nobody flinched when Nancy spoke up; people treated her with the same respect accorded to everybody else. Thanks to these emotional connections, Nancy's life was transformed. She followed no diet plan; no pills, potions, or ab-crunching exercises played a part. There was no silver bullet, no magical, elusive ingredient—yet Nancy has lost more than 530 pounds. Nancy's tale is one of redemption, a story of reevaluating her worth and insisting she had value simply because she was human. It will show a growing America that life is sweet and always worth living.